Health‐related quality of life following total minimally invasive, hybrid minimally invasive or open oesophagectomy: a population‐based cohort study. Issue 6 (9th October 2020) - Klevebro, F; Kauppila, J H; Markar, S; Johar, A; Lagergren, P
Abstract : All patients operated for oesophageal cancer in Sweden from 2013 to April 2018 were identified, and 246 patients were recruited to this population‐based nationwide Swedish study. The results show that longitudinal health‐related quality of life after minimally invasive oesophagectomy was similar to that of the open surgical approach. QoL, quality of life. No difference Abstract: Background: Minimally invasive oesophagectomy has been shown to reduce the risk of pulmonary complications compared with open oesophagectomy, but the effects on health‐related quality of life (HRQoL) and oesophageal cancer survivorship remain unclear. The aim of this study was to assess the longitudinal effects of minimally invasive compared with open oesophagectomy for cancer on HRQoL. Methods: All patients who had surgery for oesophageal cancer in Sweden from January 2013 to April 2018 were identified. The exposure was total or hybrid minimally invasive oesophagectomy, compared with open surgery. The study outcome was HRQoL, evaluated by means of the European Organisation for Research and Treatment of Cancer questionnaires QLQ‐C30 and QLQ‐OG25 at 1 and 2 years after surgery. Mean differences and 95 per cent confidence intervals were adjusted for confounders. Results: Of the 246 patients recruited, 153 underwent minimally invasive oesophagectomy, of which 75 were hybrid minimally invasive and 78 were total minimally invasive procedures. After adjustment for age, sex, Charlson Co‐morbidity Index score, pathological tumour stage and neoadjuvant therapy, there were no clinically and statistically significant differences in overall or disease‐specific HRQoL after oesophagectomy between hybrid minimally invasive and total minimally invasive surgical technique versus open surgery. Conclusion: In this population‐based nationwide Swedish study, longitudinal HRQoL after minimally invasive oesophagectomy was similar to that of the open surgical approach.